PENINGKATKAN STRATEGI PEMASARAN DENGAN UPGRADE PACKAGING DAN VARIAN RASA PADA USAHA KERUPUK SEMANDING ROSO DI DESA SEMANDING BOJONEGORO - Edy Suhartono; Khalid Fauzi Aziz; Muhammad Rizqi Agustino; Azhari Azhari; Fahrizal Taufiqqurrachman (LPPM Universitas Islam Darul 'Ulum Lamongan, 2022)
Small and Medium Enterprise (SME) are parties that have a large share in the movement of the national economy. (SME) have contributed to increasing national income, employment, increasing income for people who have low incomes and utilizing the ability to use local raw materials to produce goods and services for the wider community. Rice cracker products and shrimp paste onion crackers which are located in Semanding Village, Bojonegoro District, Bojonegoro Regency during this pandemic have not succeeded in increasing orders from consumers because the marketing of these cracker products is still limited to markets and buying and selling centers in the surrounding area. The problems faced by these cracker (SME) include that the cracker marketing strategy is still limited and not optimal, which has resulted in a minimum audience of people who are familiar with the Semanding Roso Cracker (SME) product. The methods used in the implementation of this community service activity are 1) counseling on marketing strategies and marketing costs by providing information about effective and efficient business management through promotional strategies, as well as explaining information about marketing costs. 2) Dissemination of marketing techniques by providing information on the benefits of upgrading packaging and product variants, and 3) evaluating the results of activities on the ability of participants to make good marketing strategies to increase product sales turnover and evaluation of the ability of participants to allocate marketing costs so that participants can calculate profit and loss correctly. The result of this community service program activity is the mastery of business management strategies in the field of marketing in the development of (SME) Krupuk Semanding Roso products with rice crackers and shrimp paste crackers so that (SME) Krupuk Semanding Roso in Semanding Village, Bojonegoro District, Bojonegoro Regency are more productive in developing their business .